An electrode and use thereof - Davis, Jason; Bueno, Paulo Roberto [UNESP] (Instituto Nacional de Propriedade Industrial (INPI), 2013)
The application relates to an electrode for use in the electrochemical detection of a target species, wherein the electrode has a planar surface disposed on which are probe molecules that are capable of binding selectively to the target species, wherein the electrode, prior to binding of the probe molecules with the target species, has an electron transfer resistance per area of the electrode of from 10 megaohms cm-2 to 95 megaohms cm-2.
Processo: WO2013164611
Número de publicação: WO2013164611 (A1)
Número de aplicação: WO2013GB51121